HBV Genotype: A Significant Risk Factor in Determining Which Patients With Chronic HBV Infection Should Undergo Surveillance for HCC: The Hepatitis B Alaska Study. Issue 6 (20th September 2021) - McMahon, Brian J.; Nolen, Leisha D.; Snowball, Mary; Homan, Chriss; Negus, Susan; Roik, Elena; Spradling, Philip R.; Bruden, Dana
Abstract : Background and Aims: Information is limited regarding HBV genotype and the outcome of chronic HBV (CHB) infection. We examined the effect of HBV genotype on HCC occurrence in Alaska Native (AN) persons with CHB, where five HBV genotypes are found: A2, B6, C2, D, and F1. Approach and Results: We calculated HCC incidence per 1, 000 person‐years of follow‐up to determine which groups by age, sex, and genotype met current American Association for the Study of Liver Diseases (AASLD) HCC surveillance criteria. We used Poisson regression to compare HCC risk by genotype, age, sex, and Alaska region. Incidence of HCC was calculated using the sex‐specific AASLD cutoff recommended for the Asian population of 50 years for women and 40 years for men. HCC screening was conducted semiannually using alpha‐fetoprotein levels and abdominal ultrasound. Among 1, 185 AN persons, median follow‐up was 35.1 years; 667 (63%) were male. The HBV genotype distribution was 49% D, 18% F, 13% A, 6% C, 3% B, 0.1% H, and 12% undetermined. Sixty‐three cases of HCC occurred. HCC incidence for genotype F was 5.73 per 1, 000 person‐years of follow‐up, followed by 4.77 for C, 1.28 for A, 0.47 for D, and 0.00 for B. The HCC risk was higher for genotypes F (relative rate [RR], 12.7; 95% CI, 6.1‐26.4), C (RR, 10.6; 95% CI, 4.3‐26.0), and A (RR, 2.9; 95% CI, 1.0‐8.0) compared to genotypes B and D. Among men < 40 years of age and women < 50 years of age, genotype F had the highest incidence (4.79/1, 000 person‐years). Conclusions: HBV genotype was strongly associated with HCC. HBV genotype should be considered in risk factor stratification.